Ergonomic design of a portable tile installer for tiling works - Mohd Roshdi, Farrah Rina; Mohtar, Azlin Muzliza; Mohd Fuad, Afiq Aiman; Abd Rahim, Fatin Syazwani; Abdul Talib, Nurul Husnina (2025)
Tile installation entails the systematic and careful placement of tiles on a prepared surface with suitable materials. This procedure encompasses measuring and cutting tiles to the specified dimensions, making an appropriate cement mortar or glue, arranging tiles meticulously, and ultimately scrubbing and cleaning the tiles to achieve superior quality. In construction, tile installation is a crucial element in creating an aesthetically pleasing and robust building structure. Nonetheless, tile installation necessitates a significant degree of proficiency. For instance, tile cutting and tile installation. Consequently, we have created and engineered a tile installation station solution that addresses this issue. A tile installation station is a device that facilitates the application of adhesive to the surfaces of floors repetitively with enhanced precision and efficiency. This product is user-friendly and does not necessitate advanced experience. This product can enhance tile installation tasks. The materials utilised in the development of this product include C-channel and aluminium plate. This product employs a gear mechanism to modify its height. This device can expedite tile installation. Furthermore, this product is user-friendly, and the tile installation will be more orderly. This product can significantly influence the construction industry.